Penguatan Generasi Qur’ani Melalui Kegiatan Haflatul Tilawatil Al-Qur’an (HTQ) Kabupaten Poso Di Gontor Kampus 11 - Hafizh Raafi; Ihwan Mahmudi; Idam Mustofa; Ahmad Saifulloh; Syarifah Syarifah; Riza Ashari (CV. Dalle’ Deceng Abeeayla, 2026)
Haflatul Tilawatil Al-Qur’an (HTQ) is a program designed to nurture a generation well-versed in the Quran, aiming to enhance students' abilities to read, memorize, and grasp the values within the Quran. This study seeks to examine the implementation of HTQ activities at various institutions such as TPA, TPQ, and Madrasah Ibtidaiyyah throughout Poso District, which took place at Gontor Campus 11 to facilitate the cultivation of a Quranic generation. The approach taken is Participatory Action Research (PAR), involving students, mentors, parents, organizers, and community leaders. Data was gathered using techniques such as observation, interviews, group discussions, and documentation, followed by descriptive qualitative analysis. The findings reveal that HTQ activities significantly boost reading skills, Quran memorization, understanding of Islamic values, as well as foster religious character, self-confidence, and social skills among participants. This initiative also enhances cooperation among educational institutions, families, and communities in supporting Quranic education. However, challenges still exist in terms of facilities and ongoing training that require further attention. Thus, it is essential for HTQ activities to be developed in a systematic and continuous manner to help create a high-quality Quranic generation.